2021
DOI: 10.1002/nme.6821
|View full text |Cite
|
Sign up to set email alerts
|

A novel phase‐field based cohesive zone model for modeling interfacial failure in composites

Abstract: The interface plays a critical role in the mechanical properties of composites.In the present work, a novel phase-field based cohesive zone model (CZM) is proposed for the cracking simulation. The competition and interaction between the bulk and interfacial cracking are taken into consideration directly in both displacement-and phase-field. A family of modified degradation functions is utilized to describe the traction-separation law in the CZM. Finite element implementation of the present CZM was carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Then, the cracking in the bulk is described by a brittle model, while the interface behaviour is modelled by the cohesive model. [33][34][35][36][37][38] The cohesive phase-field model of Verhoosel and de Borst 19 and Nguyen et al 25 uses the phase-field regularisation technology to transform a discrete interface into a smeared one. The cohesive law is incorporated in a displacement jump-dependent fracture energy function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the cracking in the bulk is described by a brittle model, while the interface behaviour is modelled by the cohesive model. [33][34][35][36][37][38] The cohesive phase-field model of Verhoosel and de Borst 19 and Nguyen et al 25 uses the phase-field regularisation technology to transform a discrete interface into a smeared one. The cohesive law is incorporated in a displacement jump-dependent fracture energy function.…”
Section: Introductionmentioning
confidence: 99%
“…In the brittle fracture model the cohesive interface debonding and the cracking in the bulk can also be considered separately. Then, the cracking in the bulk is described by a brittle model, while the interface behaviour is modelled by the cohesive model 33–38 …”
Section: Introductionmentioning
confidence: 99%
“…The showed that this approach is feasible to achieve high load-carrying capacity when increasing clay nanoparticle volume fraction, aspect ratio or alignment of the particles. Bian et al [23] proposed a phase-field based cohesive zone model to account for cracking simulation. This approach is able to not only account for bulk cracks but also for interfacial cracks.…”
Section: Introductionmentioning
confidence: 99%